HOW TO TEACH YOUNG GENERATION TO LEARN FOREIGN LANGUAGES EASILY - Mamasodiqova Muxlisaxon,; Sirojiddinova Shaxribonu Sirojiddinovna, (Лучшие интеллектуальные исследования, 2023)
Abstract: This article suggest several types of beneficial ways in support of preparing children to master foreign languages and improve their language skills